Um estudo sobre a busca pelo personagem do telejornal JPB 1ª edição da TV Cabo Branco - Souza, Bruna Fernandes de (2017)
It is usual to watch on the news ordinary people, who are not experts or authorities, providing testimony, telling facts of their lives, talking about different topics. They are the characters that support and humanize the reports. In this study, we try to understand how is the presence of this character in the television news. The object of study is the television news JPB 1st edition, transmitted by Cabo Branco TV, an affiliate of Rede Globo in Paraiba. The research ranges from the search process to find these characters, approaching the journalistic routines of the newsroom, to the inclusion of these individuals in the reports. Other goals we tried to achieve were to identify the tools used to find the characters, understand the interaction of the TV producers with new means to search and contact, especially social networks, and reflect on ways to improve the process of searching and selecting characters. Therefore, we use concepts and theories that deal with issues of humanization of journalism, participation and approach of the public with journalistic practices. It is a qualitative and exploratory research, which included bibliographic research, interviews and questionnaires with journalists of the newsroom, especially producers, as well as analysis of that television news reports. It was also used the participant observation method.